Inventory Controls and Financial Performance of the Private Education Development Network Mbale Branch Under Usaid - Nahyuha Victoria Joyce (Uganda Christian University, 2024)
Good performance of PEDN is critical due to the important role that management plays. The study assessed the effect of inventory control on financial performance in PEDN Mbale branch. The specific objectives were to establish the effect of inventory recording on financial performance of PEDN Mbale, to determine the effect of stock audit on financial performance of PEDN Mbale and to examine the effect of inventory management training on financial performance of PEDN Mbale. The study adopted a descriptive research design. The target population of the study was 85 employees in PEDN Mbale. The sample size was 70 employees in PEDN Mbale who were selected using stratified random sampling. Primary data was collected through the administration of the questionnaires. After quantitative data was obtained through questionnaires, it was prepared in readiness for analysis by editing, handling blank responses, coding, categorizing and keyed into statistical package for social sciences (SPSS) computer software for analysis. The statistics generated included descriptive and inferential statistics. The study found that inventory recording has a positive and a significant effect on financial performance. The study found that stock taking have a positive and a significant effect on financial performance. The study found that inventory management training has a positive and a significant effect on financial performance. The study concluded that highly automated organizations perform better than an organization that still uses manual systems. The study recommends that there should be transparency in stock audit in PEDN Mbale. In addition, all activities should be automated so as to improve performance of PEDN.